Analisis Proses Berpikir Siswa dalam Memecahkan Masalah Matematika berdasarkan Langkah-Langkah Bransford dan Stein ditinjau dari Adversity Quotient - Yanti, Avissa Purnama; Syazali, Muhamad (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
This study aims to describe the thinking process of students of MAN I Bandar Lampung based on Adversity Quotient (AQ) type climbers, campers and quitters in solving mathematical problems based on Bransford and Stein theories on equations and quadratic functions. This research is a qualitative descriptive research. Research subjects were determined through purposive sampling, and this research was conducted in class X MIA 4 MAN I Bandar Lampung with subject of 6 students divided into 3 groups. The first group consisted of 2 students of type climbers, the second group consisted of 2 students of campers, and the third group consisted of 2 students of type quitters. To determine the type of Adversity Quotient (AQ) of the subject to be selected, the ARP test is used. The data collection technique in this study uses the test method, unstructured interview method conducted on selected subjects and documentation method. Data analysis techniques through data reduction, data presentation, and conclusions. Written test result data is analyzed based on indicators that meet conceptual, semiconceptual, and computational thinking processes. The technique of data validity is done by using triangulation technique comparing data of test result and interview result to subject of climbers, campers and quitters. Based on the data analysis results obtained that the subject with the type Adversity Quotient (AQ) each has a different thinking process. Subjects with type climbers tend to have a conceptual thinking process in solving mathematical problems based on Bransford and Stein theories. Subjects with type campers tend to have a semiconceptual thinking process in solving mathematical problems based on Bransford and Stein theories, and subjects with type quitters in solving problems based on Bransford and Stein theories tend to have a computational thinking process.